KAJIAN ALKITABIAH MENGENAI PENGAJARAN ORANG TUA DALAM PEMBENTUKAN KARAKTER ANAK - Oklis Sirva; Karnila Yesita Pariu; Natalia Parangki; Andarias Jeli Patoding; Febrian Tandi Puang (CV. Adiba Aisha Amira, 2023)
In the context of an ever-evolving social and cultural landscape, the education of children becomes a primary concern in shaping character and fostering the faith of the younger generation. This research aims to conduct an in-depth analysis of the Bible's perspective on the role of parents in the education of their children. Through this study, the researcher will explore and examine various relevant Bible texts, such as verses detailing parental responsibilities, pedagogical principles, and moral guidance found in the Bible. The research methodology to be employed includes critical and theological analysis of Bible texts, as well as an exploration of the meaning and historical context of verses relevant to the practice of parental education. The results of this research are expected to provide a better understanding of the role and responsibilities of parents in shaping the character, morals, and spirituality of their children in accordance with Biblical principles. Furthermore, this research may offer practical guidance to parents, churches, and Christian communities in strengthening family relationships and supporting faith-based education. In conclusion, this research will deepen our understanding of parental education from a Biblical perspective, which can influence family education practices in the future.